Analisis Implementasi SOP Pasasi PT Jasa Angkasa Semesta dalam Pelayanan Penumpang di Bandar Udara Internasional Juanda Surabaya - Azza, Zuhrufa Dian; Laksana, Andityo Pujo (Economic Reviews Journal, 2024)
Ground Handling is an activity of a flight company related to handling or services to passengers such as baggage, tickets and equipment for aircraft movement on the ground and the aircraft it self while at the airport both departure and arrival. The cassation unit is part of Ground Handling which has duties and responsibilities in handling passengers from the check-in process to boarding passengers, as well as handling the process of transit passengers. This study is to find out how the role of PT Angkasa Semesta services in serving passengers at Juanda International Airport Surabaya. This research is a descriptive qualitative research. The data used are primary and secondary data. Primary data include direct observation of the research object and interviews with pasasi officers. While secondary data is taking data when conducting observations and interviews such as how cassation staff work in the field and SOPs of the cassation unit related to services to passengers. The results of this study can be concluded that the role of PT Jasa Angasa semesta in passenger services at Juanda International Airport Surabaya is in accordance with the existing Procedur Operational Standards. Ground Handling officers carry out services from the check-in counter to the departure gate, supervise passenger movements on the landside and coordinate with AVSEC, AMC and RAMP. Obstacles experienced by PT Jasa Angkasa Semesta is constrained by foreign languages and then lacks the number of personnel.